2020
DOI: 10.1371/journal.pone.0237547
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotics in caries prevention: A scoping review

Abstract: The scoping review aimed to examine the evidence on the role of synbiotics in caries prevention. PubMed, SCOPUS, and Web of Science databases search were performed. Any in vitro study, clinical trial, systematic review with/without meta-analysis, umbrella review/ meta-evaluation, narrative review addressing the role of synbiotics in caries prevention were included in the scoping review. Data were extracted from the included studies using pre-approved registered protocol. Twenty-eight records were identified, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…As per WHO, probiotics are defined as "live micro-organisms which when administered in adequate amounts confer a health benefit on the host". 11 Several invitro studies examining the effect of probiotics on caries prevention have been conducted in the last two decades using different probiotics strains and species; however, probiotic colonization in the oral cavity is transient. Therefore, formulations enhancing probiotics survival are needed to impart long-standing cariespreventive benefits.…”
Section: Discussionmentioning
confidence: 99%
“…As per WHO, probiotics are defined as "live micro-organisms which when administered in adequate amounts confer a health benefit on the host". 11 Several invitro studies examining the effect of probiotics on caries prevention have been conducted in the last two decades using different probiotics strains and species; however, probiotic colonization in the oral cavity is transient. Therefore, formulations enhancing probiotics survival are needed to impart long-standing cariespreventive benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Since lactobacilli are often considered late colonizers of the pellicle, probiotics alone are insufficient to prevent cavities [10,11]. To accelerate the use of conventional probiotics, which have well-characterized and well-documented health benefits, an adjuvant for that promotes the colonization of probiotics while modulating the virulence factor of the pathogen is necessary [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Prebiotics impact the functional potential of bacterial cells [15,16]. Therefore, probiotics are in a combination of prebiotics (referred to as synbiotics), that synergically modulate the virulence of S. mutans and, in turn, inhibit cariogenic biofilm formation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Biotic strategies-prebiotics, probiotics, and synbiotics-are being explored as supplementary interventions to the long-known effects of fluorides (F) on dental caries [7]. Topical F application has led to a dramatic decline in dental caries worldwide [8,9]; however, its antimicrobial effect on cariogenic biofilms is limited [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Topical F application has led to a dramatic decline in dental caries worldwide [8,9]; however, its antimicrobial effect on cariogenic biofilms is limited [10,11]. The caries-preventive potential of synbiotics is still in the pre-clinical investigation stages [7], while probiotics are effective on pathogenic biofilms [12][13][14], with brief sustainability in the oral cavity [13,14]. The role of prebiotics in caries prevention (through clinical trials) has been explored over the past two decades, with reported superior caries-preventive potential than fluoride [15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%